Application of Double Track System Model Against Applicants of Narcotics Abus - Tony Andri Dwi Ermawan; Ira Alia Maerani; Achmad Sulchan (Universitas Islam Sultan Agung, 2022)
The purpose of this study is to find out and analyze the implementation of the implementation of the double track system model against narcotics abusers. To find out and analyze the obstacles and solutions to implementing the double track system model for narcotics abusers. This study uses a sociological juridical approach, with descriptive analytical research specifications. The data used in this study was secondary data obtained through literature study which was then analyzed qualitatively. The results of this study were the application of the double track system model of law against perpetrators of narcotics abuse in the form of applying the law to serve a sentence in prison, while the sanctions for actions given to narcotics addicts as victims are in the form of treatment and/or treatment organized in the form of rehabilitation facilities. The implementation system is that the period of treatment and/or treatment is counted as a period of serving a sentence. Barriers to the Implementation of the Double Track System Model on Narcotics Abuse Perpetrators are the existence of different rules that can be applied to the same act, namely narcotics abuse; inadequate infrastructure; rehabilitation institutions for narcotics abuse and narcotics victims are still very limited.